Strengthening of the Basic Soil (Sub Grade) of the Road Using Galam Piles - Muhammad Suhaimi; Sofwan Hadi; Ahmad Rizani; Salmani; Fentasia, Detta Tianida Fentasia; Abdul Hafizh Ihsani (PT FORMOSA CENDEKIA GLOBAL, 2023)
Banjarmasin City is situated on an alluvial soil type characterized by clay structures with a relatively low soil carrying capacity; hence, soil stabilization is required. The soil is stabilized using a variety of techniques. Stabilization techniques include using geotextiles, columns, sand stabilizing the soil itself, and stabilizing concrete mix. Implementation at the existing project site is stability stable pending catastrophe. In order the soil's carrying capacity, a depression is created at a predetermined distance beneath the soil, which is generally soft. The method of implementation utilized to assist in the preparation of this research includes data collecting and analysis of the obtained results. This evaluation's data sources consist of secondary data and data processing. By utilizing a static living load of 22.68 tons and the results of the calculation, it is determined that the load acting on the road construction is 33.2415 tons. The Schmertmann- Nottingham technique (1975) yielded a Qult Single of 1.245 and a Qgroup permit of 10.27 tonnes for the carrying capacity of the Galam woodGalam with a pile depth of 5 meters